Low-Titer Type O Whole Blood for Transfusing Perinatal Patients after Acute Hemorrhage: A Case Series - Carr, Nicholas R.; Bahr, Timothy M.; Ohls, Robin K.; Tweddell, Sarah M.; Morris, David S.; Rees, Terry; Ilstrup, Sarah J.; Kelley, Walter E.; Christensen, Robert D. (American Journal of Perinatology Reports, 2024)
Objective Acute and massive blood loss is fortunately a rare occurrence in perinatal/neonatal practice. When it occurs, typical transfusion paradigms utilize sequential administration of blood components. However, an alternative approach, transfusing type O whole blood with low anti-A and anti-B titers, (LTOWB) has recently been approved and utilized in trauma surgery.Study Design Retrospective analysis of all perinatal patients who have received LTOWB after acute massive hemorrhage at the Intermountain Medical Center.Results LTOWB was the initial transfusion product we used to resuscitate/treat 25 women with acute and massive postpartum hemorrhage and five infants with acute hemorrhage in the first hours/days after birth. We encountered no problems obtaining or transfusing this product and we recognized no adverse effects of this treatment.Conclusion Transfusing LTOWB to perinatal patients after acute blood loss is feasible and appears at least as safe a serial component transfusion. Its use has subsequently been expanded to multiple hospitals in our region as first-line transfusion treatment for acute perinatal hemorrhage.Key PointsLow-titer type O whole blood (LTOWB) was our initial transfusion product for 30 perinatal patients with acute hemorrhage. Twenty-five of these were obstetrical patients and five were neonatal patients. We encountered no problems with, or adverse effects from LTOWB in any of these patients. LTOWB transfusions to women were ten days since donor draw (interquartile range, 8–13) and to neonates was six days (5–8).
Keywords: transfusion; whole blood; perinatal; neonatal; hemorrhage